Immunogenicity and safety of SARS-CoV-2 vaccine in hemodialysis patients: A systematic review and meta-analysis - Peiyao, Ren; Mengjie, Yu; Xiaogang, Shen; Wenfang, He; Danna, Zheng; Yuqun, Zeng; Juan, Jin; Qiang, He (Frontiers in Public Health, 2022)
Rationale & Objective: COVID-19 vaccine is one of the most effective ways to prevent COVID-19. We conducted this study to investigate the immunogenicity and safety of the COVID-19 vaccine in dialysis patients. Methods: We systematically searched PubMed, MEDLINE, EMBASE and Cochrane Library for cohort, RCTs and cross-sectional study. The data of immunogenicity rate, antibody titer, survival rate, new infection rate, adverse events, type of vaccine, and patients’ characters such as age, sex, dialysis vintage, immunosuppression rate, prevalence of diabetes were extracted and has been analyzed by REVMAN 5.4 and Stata software. Random-effects meta-analysis was used to perform the research. Results: The overall immunogenicity of dialysis patients was 87% (95%CI, 84%-89%). Vaccine response rates were 85.1% in HDPs (1201 of 1412), and 97.4% in healthy controls (862 of 885). The serological positive rate of infection-naïve was 82.9% (777 of 937), and 98.4% (570 of 579) in patients with previous infection. The SMD of antibody titers in dialysis patients with or without previous COVID-19 infection is 1.14 (95% CI:0.68-1.61). Subgroup analysis showed that immunosuppression rate was an influential factor affecting the immunogenicity rate (P<0.0001). Nine studies reported safety indexes, among which 4 local adverse events and 7 system adverse events were documented. Conclusions: Vaccination helped dialysis patients achieve effective humoral immunity, with an overall immune efficiency of 87.5%. Dialysis patients may suffer a variety of adverse events after vaccination, but the incidence of malignant events is very low, and there is no report of death or acute renal failure after vaccination.